Economic Structure and Development of the Pilsen City Region and Marginal Areas in the Pilsen - Dokoupil, Jaroslav (Journal for Geography, 2006)
The organizational structure of the economy has changed in the Pilsen district. There are differences in the professional structure and size of the structure. Foreign investments play an important role, developing differently in the Pilsen city region and in the border districts. The development of unemployment and population structure also do not follow the same graphs in relation to the quality of traffic situation, economic structure, and preparation for foreign investments.
Keywords: Agglomeration; border districts; Pilsen; Czech Republic